Strategic Plan of the Canadian Institutes of Health Research Institute of Nutrition, Metabolism, and Diabetes - Philip M Sherman; Mary-Jo Makarchuk; Paul Belanger; Eve A Roberts (Canadian Journal of Gastroenterology)
The present document provides the new and updated strategic plan for the Institute of Nutrition, Metabolism, and Diabetes (INMD) of the Canadian Institutes of Health Research. This plan provides an overarching map for the strategic activities of the INMD during the five years from 2010 to 2014. These strategic priorities will guide the way that the INMD uses its resources over this period of time, and will provide opportunities to build new partnerships and strategic alliances that enhance and leverage the capacity to fund targeted research initiatives.